Analyzing whether the personality characteristics of young university entrepreneurs candidates are compatible with entrepreneurship in terms of career - Adıgüzel, Zafer; Zehir, Cemal; Musluhittinoğlu, Nisa Nur (Beta Basım Yayım Dağıtım A.Ş., 2021)
Purpose: To evaluate the potential of university students in entrepreneurship and to analyze students’ entrepreneurshipthoughts.Methodology: Within the scope of the research, a survey was conducted with 510 university students. After factor andreliability analysis was done, using SPSS 25 and AMOS Program, path analysis was performed.Findings: In the findings of the research, it can be concluded that the personality characteristics, innovativeness,thoughts and desires of success of university students are effective in choosing entrepreneurship as a career step.Practical Implications: Mediation effect and personality characteristics, innovativeness, and need for achievementvariables have a positive effect. The results of the study show that, in terms of the effects of personality characteristics onyoung people, cultural studies should also be conducted.Originality: The article is intended to provide practical results using quantitative research methods along with theoreticalinformation regarding variables. This study shows that university students prefer entrepreneurship ion their career path.

Amaç: Üniversite öğrencilerinin girişimcilik konusundaki potansiyellerinin değerlendirilebilmesi ve öğrencilerin girişimcilik düşüncelerini analiz etmek amacıyla yapılmıştır. Yöntem: Araştırmanın amacı kapsamında 510 üniversite öğrencisi ile anket çalışması yürütülmüştür. SPSS 25 ve AMOS Programı kullanılarak faktör ve güvenirlilik analizi yapıldıktan sonra, korelasyon analizi ve regresyon analizi yapılmıştır. Bulgular: Araştırmada elde edilen bulgularda, üniversite öğrencilerinin genel anlamda kişilik özelliklerinin, yenilikçi düşüncelerinin ve başarılı olma arzularının kariyer adımı olarak girişimciliği seçmelerinde etkili olduğu sonucuna varılabilmektedir. Sonuç: Yenilikçilik ve başarı ihtiyacı değişkenlerinin aracı etkisi ve kişilik özelliklerinin olumlu yönde etkisi vardır. Çalışma sonuçları kişilik özelliklerinin gençler üzerindeki etkileri bakımından kültürel boyutta da araştırmalar yapılması gerektiğini göstermektedir. Özgün Değer: Makalede değişkenlerle ilgili teorik bilgilerle birlikte, aynı zamanda nicel araştırma yöntemi kullanıldığından dolayı pratik sonuçlar sağlaması amaçlanmıştır. Bu çalışma, üniversiteli gençlerin kariyer yolunda girişimciliği tercih ettiklerini göstermektedir.
Üniversiteli genç girişimci adaylarının sahip oldukları kişilik özelliklerinin kariyer açısından girişimcilik ile uyumlu olup olmadığının analiz edilmesi
Keywords: Personality Characteristics; Need for Achievement; Innovativeness; Entrepreneurship; Kişilik Özellikleri; Başarı İhtiyacı; Yenilikçilik; Girişimcilik